3 ( 2x + 4 ) = 4 ( x + 6)
Soluções para a tarefa
Respondido por
18
Boa noite!!
![3(2x + 4) = 4(x + 6) \\ 6x + 12 = 4x + 24 \\ 6x - 4x = 24 - 12 \\ 2x = 12 \\ x = \frac{12}{2} \\ x = 6 3(2x + 4) = 4(x + 6) \\ 6x + 12 = 4x + 24 \\ 6x - 4x = 24 - 12 \\ 2x = 12 \\ x = \frac{12}{2} \\ x = 6](https://tex.z-dn.net/?f=3%282x+%2B+4%29+%3D+4%28x+%2B+6%29+%5C%5C+6x+%2B+12+%3D+4x+%2B+24+%5C%5C+6x+-+4x+%3D+24+-+12+%5C%5C+2x+%3D+12+%5C%5C+x+%3D++%5Cfrac%7B12%7D%7B2%7D++%5C%5C+x+%3D+6)
Bons estudos :)
Bons estudos :)
Respondido por
5
Resposta:
S = { 6 }
Explicação passo-a-passo:
.. Equação de 1° grau:
.. 3.(2x + 4) = 4.(x + 6)
.. 6x + 12 = 4x + 24
.. 6x - 4x = 24 - 12
.. 2x = 12
.. x = 12 : 2........=> x = 6
Perguntas interessantes
Ed. Física,
10 meses atrás
Geografia,
10 meses atrás
Matemática,
10 meses atrás
Filosofia,
1 ano atrás
Física,
1 ano atrás
Filosofia,
1 ano atrás